Judging Bertha Wilson : Law as Large as Life. - Anderson, Ellen (Osgoode Society for Canadian Legal History., 2002)
Supported with the warmth and generosity of Wilson's numerous personal anecdotes, this work illuminates the life and thought of a woman who has left an extraordinary mark on Canada's legal landscape.